VISIONS OF THE INCLUSIVE SCHOOL : Preferred futures by special education teacher students - Nikula, Elina (My University, 2020)
This Master’s thesis examined the preferred future of inclusive education. Inclusive education is a universal political goal indicated by internationally agreed declarations. The meaning of inclusive education is linked to equality of access to education generally regardless of students’ individual qualities and is about the presence, participation, and achievement of all students in joint environments. In Finland, the number of pupils with special educational needs has increased in recent decades, at the same time as many special schools have been closed. However, the definition of the concept of inclusion and the means to achieve it are still under discussion. There is disagreement, how inclusive teaching is put into practice, and whether it works equally for all students in need of support. By identifying the aspects connected to a preferable future of inclusive education, this study has been aimed to go beyond the problem-oriented discourse of inclusive education and raised awareness of multiplicity about the theme. A qualitative approach was used to explore the values and factors identified important by special education teacher students about the preferable future of inclusive education. The topic was studied empirically in three similarly implemented futures workshops in 2019. The qualitative content analysis was used as a basis of the data analysis. The essential values were compared to Booth’s typology of inclusive values and the key factors needed in desired inclusive education were identified in inductive content analysis forming three partially overlapping dimensions: structural, social, and emotional dimensions. These dimensions are intertwined and must be considered equally important in the development of inclusive education. The thesis argues for promoting participation and communality in school environments. Also, structural factors, such as the impact of physical environments, more equal distribution of resources, and shared leadership, need to be considered more strongly in the future.

Tässä opinnäytetyössä tarkasteltiin inklusiivisen koulun toivottua tulevaisuutta. Inklusiivinen koulutus on yleismaailmallinen poliittinen tavoite, johon on sitouduttu kansainvälisin julistuksin. Inklusiivisen koulutuksen merkitys liittyy tasa-arvoiseen koulutukseen osallistumiseen opiskelijoiden yksilöllisistä ominaisuuksista riippumatta, ja se koskee kaikkien opiskelijoiden osallistumista, osallisuutta ja toimintaa yhteisissä ympäristöissä. Suomessa keskustellaan inklusiivisen koulutuksen käsitteen määrittelystä ja keinoista sen saavuttamiseksi. On erimielisyyksiä siitä, miten inklusiivinen opetus toteutetaan käytännössä ja toimiiko se todella yhtäläisesti kaikkien tukea tarvitsevien opiskelijoiden kanssa. Tunnistamalla inklusiivisen koulun toivottuun tulevaisuuteen liittyvät näkökohdat, tämän tutkimuksen tarkoituksena on päästä inklusiivisen koulutuksen ongelmakeskeisestä keskustelusta ja lisätä tietoisuutta aiheen moninaisuudesta. Tässä laadullisessa tutkimuksessa tavoitteena oli tutkia arvoja ja tekijöitä, jotka erityisopettajaopiskelijat tunnistivat tärkeiksi inklusiivisen koulun tulevaisuuden kannalta. Aihetta tutkittiin empiirisesti kolmessa yhtäläisesti toteutetussa tulevaisuustyöpajassa vuonna 2019. Data-analyysin perustana käytettiin kvalitatiivista sisällönanalyysiä. Keskeisiä arvoja verrattiin Boothin osallistavien arvojen typologiaan ja toivotun inklusiivisen koulun kannalta tärkeimmät tekijät tunnistettiin induktiivisessa sisällönanalyysissä muodostamalla kolme osittain päällekkäistä ulottuvuutta: rakenteellinen, sosiaalinen ja emotionaalinen ulottuvuus. Nämä ulottuvuudet ovat kietoutuneet toisiinsa ja niitä on pidettävä yhtä tärkeinä inklusiivisen koulun kehittämisessä. Tulosten perusteella osallisuuden ja yhteisöllisyyden edistäminen kouluympäristössä edistää inkluusiota koulussa. Lisäksi rakenteellisia tekijöitä, kuten fyysisen ympäristön vaikutuksia, tasa-arvoisempaa resurssien jakoa ja jaettua johtajuutta, on tulevaisuudessa harkittava voimakkaammin.
Keywords: inclusion, inclusive education, preferred future, future of education